Acanthosis Nigricans: An Updated Review - Leung, Alexander K.C.; Lam, Joseph M.; Barankin, Benjamin; Leong, Kin F.; Hon, Kam Lun (Current Pediatric Reviews, 2023)
Background: Early recognition of acanthosis nigricans is important because acanthosis nigricans can be a cutaneous manifestation of a variety of systemic disorders and, rarely, as a sign of internal malignancy. Objective: The purpose of this article is to familiarize pediatricians with the clinical manifestations, evaluation, diagnosis, and management of acanthosis nigricans. Methods: A search was conducted in November 2021in PubMed Clinical Queries using the key term
Keywords: retinoids